Enteral resorbable diet versus standard diet in primary sphincter reconstruction: a prospective randomised trial - Joos, Andreas; Bussen, Dieter; Galata, Christian; Reißfelder, Christoph; Herold, Alexander; Seyfried, Steffen (International journal of colorectal disease, 2021)
Method Adult patients undergoing elective fistulectomy with primary sphincter reconstruction for anorectal and rectovaginal fistulas were eligible for inclusion. Patients were intraoperatively randomised to receive either the ED and peristalsis-inhibiting medication (ED) or a SD. The primary endpoint was the healing rate. Secondary endpoints included continence scores, complications and quality of life. Sample size calculation resulted in the analysis of 60 patients to detect a difference in fistula recurrence of 30% with 70% power and a 5% significance level. - Results Sixty-six patients (24 women) were prospectively and randomly assigned to the ED (n = 34: 51%) or a SD (n = 32; 48%); mean age was 47 (18-74) years. The primary healing rate was 64 out of 66 patients (96%). No statistical difference in healing rate was seen between the groups. However, patient satisfaction was significantly higher in the SD group (P < 0.0001). - Conclusions Fistulectomy with primary sphincter reconstruction is a safe method with low complication rates. Postoperative stool behaviour has no significant influence on the healing rate but has a significant negative impact on patient satisfaction. Therefore, maintaining a standard diet seems to be preferable following reconstructive anal surgery.